Techno-economic analysis of producing xylo-oligosaccharides and cellulose microfibers from lignocellulosic biomass. (November 2021) - Lan, Kai; Xu, Yiling; Kim, Hoyong; Ham, Choonghyun; Kelley, Stephen S.; Park, Sunkyu
Highlights: Producing XOS from miscanthus by autohydrolysis and purification. Assessing the economic viability under varied XOS content and system configurations. High-value byproduct presents promising opportunity in reducing cost. Key drivers of economic performance are identified. Potential improvement pathways of reducing cost are presented. Abstract: This study assesses the economic performance of a biorefinery producing xylo-oligosaccharides (XOS) from miscanthus by autohydrolysis and purification based on a rigorous model developed in ASPEN Plus. Varied biorefinery capacities (50–250 oven dry metric ton (ODMT)/day) and three XOS content levels (80%, 90%, 95%) are analyzed. The XOS minimum selling price (XOS MSP) is varied between $3, 430–$7, 500, $4, 030–$8, 970, and $4, 840–$10, 640 per metric ton (MT) for 80%, 90%, and 95% content, respectively. The results show that increasing biorefinery capacity can significantly reduce the XOS MSP and higher purity leads to higher XOS MSP due to less yield, and higher capital and operating costs. This study also explores another system configuration to produce high-value byproducts, cellulose microfiber, by utilizing the cellulose to produce microfiber instead of combusting for energy recovery. The XOS MSP of cellulose microfiber case is $2, 460–$7, 040/MT and thus exhibits potential economic benefits over the other cases.